Seasonal Dynamics, Parity Rate, and Composition of Culicoides (Diptera: Ceratopogonidae) Occurring in the Vicinity of Wild and Domestic Ruminants in the Czech Republic - Rádrová, Jana; Mračková, Marie; Galková, Zdenka; Lamka, Jírí; Račka, Karol; Barták, Pavel; Votýpka, Jan (Journal of medical entomology, 2016)
In the light of the emergence of bluetongue and Schmallenberg viruses in northern and central Europe, an extensive entomological survey within the framework of a bluetongue control program was undertaken from 2008 to 2013 in the Czech Republic to investigate Culicoides biting midges (Diptera: Ceratopogonidae) collected in close proximity of domestic livestock and semiwild ruminants. Insects were sampled using CDC black-light suction traps placed overnight near ruminants in farms or in forest game preserves to provide data on Culicoides fauna collected near these two groups of hosts inhabiting different environments. From almost a half million biting midge specimens collected at 41 sampling sites, 34 species were identified including three species newly recorded for the Czech Republic: Culicoides (Oecacta) clastrieri Callot, Kremer & Deduit, Culicoides (Oecacta) odiatus Austen, and Culicoides (Pontoculicoides) saevus Kieffer. The Culicoides obsoletus species group, incriminated as a bluetongue virus vector, was predominant in both domestic livestock (91%) and semiwild game (52%). A relatively high proportion (around 30%) of C. obsoletus Meigen females with pigmented abdomen (= more likely parous) was observed from spring till autumn. In contrast, adult biting midges were found to be largely absent during at least three winter months, approximately December till March, which could be considered as the biting midge vector-free period.
Keywords: Cattle; skot; Česká republika; hmyz - vektory; dobytek; Czech Republic; Population Dynamics; Animals; populační dynamika; ženské pohlaví; Ruminants; roční období; Seasons; zvířata; Ceratopogonidae; Livestock; Insect Vectors; Female; přežvýkavci